Marxism - Salazar Paniagua, Freddy (Estudios de Filosofía, 1992)
An attempt is made at determining the contents of the concept of "marxism," based on the already secular history of the phenomenon known under such a name. This is achieved by means of five theses on its theoretical contents, its relationship to Marx, its origin and foundation in Engels' thought; the relationship to and distinction from the concepts of socialism and communism is specified.